Simulation-Based Pediatric Resuscitation Curriculum for Prehospital Providers - Cara Doughty; Nadia Pearson; Juan Mondragon; Jennifer Arnold; Thuy Ngo; Manish Shah (Association of American Medical Colleges, 2014)
Abstract This curriculum was developed to provide didactic and simulation-based education for prehospital providers, such as emergency medical technicians and paramedics, caring for critically ill children in the prehospital environment. The course includes a 75-minute didactic lecture focused on pediatric assessment, three pediatric skills stations highlighting differences between adult and pediatric resuscitation skills, and four high-fidelity scenarios focused on neonatal resuscitation, respiratory distress/failure, seizures, and non-accidental trauma. Each scenario is followed by a debriefing session. This curriculum was developed via collaboration between a consensus group of experts in simulation, medical education, pediatric emergency medicine, prehospital pediatrics, and emergency medical services. After initial curriculum development and instructor training, the curriculum was trialed with emergency medical services providers, and then modified based on their feedback and the feedback of the emergency medical services medical directors. This course has been taught to over 550 prehospital providers since February 2012. Posttest results show significant improvement over pretest scores, and course satisfaction surveys demonstrate extremely high learner satisfaction. Future studies are currently evaluating 6-month retention of knowledge with or without interspersed education, and clinical outcomes for patients of providers trained in this course.